Exploiting design thinking to improve energy efficiency of buildings. (15th April 2020) - Tushar, Wayes; Lan, Lan; Withanage, Chathura; Sng, Hui En Karen; Yuen, Chau; Wood, Kristin L.; Saha, Tapan Kumar
Abstract: This paper studies an interdisciplinary approach for improving building energy efficiency. In particular, the proposed approach integrates design innovation (DI) techniques, existing energy audit methods (EAM), and data-driven & engineering modeling techniques (DET) in the process of sustainable smart energy system design. From this perspective, DI methods are extended and modified to suit the content of sustainable smart energy system design and a DI 4D (Discover, Define, Develop and Deliver) framework is introduced to guide the design process. The motivation behind and the implementation procedure of each of the DI phases is explained separately, and the process of integrating DI methods, EAM and DET in developing a sustainable smart energy system is demonstrated. The proposed approach is deployed within the campus of a tertiary education institution to show its effectiveness in designing a smart sustainable energy system. Highlights: A design innovation (DI) approach is proposed for smart energy system design. A comprehensive background of the proposed DI framework is provided. How DI can be used to design smart energy system is demonstrated. Experimental case studies are provided to show the benefit of the proposed scheme.